Sustaining Himalayan agriculture under changing climate scenario - Lama, Yangdup; Agarwal, Rishu; Singh, Shishir Kumar; Arunachalam, Ayyanadar (Annals of Agricultural Research, 2017)
The biodiversity rich Indian Himalayan Region (IHR) harbours diverse culture in the lifestyle of people residing therein who have adapted to the geographic toughness and climate uncertainties over a period of time. Sustaining these humans with food and nutrition calls for focussed understanding of food production systems in the ecologically fragile environment. Further, the growing impact of climate change is marginalizing life of people despite abundance of natural resources. The paper focuses on the ecological characteristics, socio and cultural aspects and challenges of agriculture in three physiographic divisions of IHR viz., north-western Himalaya, central Himalayan and the north-eastern Himalayan region. Initiatives to promote climate resilient agriculture for sustaining the Himalayan agriculture have also been discussed in this paper.